UNDERSTANDING PALLIATIVE AND END OF LIFE CARE THROUGH STAKEHOLDER AND COMMUNITY ENGAGEMENT. Issue 1 (1st March 2014) - Layden, J; Connelly, M; Sandeman, K; Hekerem, D; Alexander, H; McLoughlin, P; Tyrrell, P
Abstract : Introduction: The pressures on palliative and end-of-life care, including the increasing elderly population; changes in illness and mortality trends; and public finances, have been well documented. Three Marie Curie palliative care service redesign initiatives in Argyll and Bute, Lanarkshire and Lothian are using a range of methods to effect improvements, including stakeholder and community engagement. Health promoting palliative care is an important concept within this changing environment. Aim(s) and method(s): Stakeholder workshops were held to identify innovative options for raising public awareness of, and promoting community involvement in death, dying and bereavement. Results: A total of 155 people attended the workshops with over 125 ideas generated. These ideas were themed and 25 are being further developed into possible service initiatives. Conclusion(s): By creating opportunities discuss to discuss death, dying and bereavement, local stakeholders were able to engage with each other to develop innovative ideas to raise public awareness of, and promote community involvement in death, dying and bereavement.